If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+1)-x=3(x+1)
We move all terms to the left:
2(x+1)-x-(3(x+1))=0
We add all the numbers together, and all the variables
-1x+2(x+1)-(3(x+1))=0
We multiply parentheses
-1x+2x-(3(x+1))+2=0
We calculate terms in parentheses: -(3(x+1)), so:We add all the numbers together, and all the variables
3(x+1)
We multiply parentheses
3x+3
Back to the equation:
-(3x+3)
x-(3x+3)+2=0
We get rid of parentheses
x-3x-3+2=0
We add all the numbers together, and all the variables
-2x-1=0
We move all terms containing x to the left, all other terms to the right
-2x=1
x=1/-2
x=-1/2
| x²+5x-3=0 | | 8j+3=100 | | 7n=20n-10 | | -(6x-3)-(5x-5)+11=-10(x-1)-(4x+9)+3 | | (3x)^2=180 | | (X+5)+(2x+3)=8 | | y−3=−3y−43 | | 3m–7=20 | | 255=54-y | | 4.50=4x | | 3x+88=187 | | 4.50x=4 | | 3x+38=187 | | 3s+9=34 | | 2,5x^2+x+1=0 | | 0.1x-0.7(4-x)=0.8 | | 5y-9=4y | | 4.5*x=4*x | | a/4+6=-4 | | 4.50x=4x | | 3x2+7x+18=0 | | 1/8x-1=x | | 744=520+28x | | 1/4x-1=2x | | 4.50x-15000=4x-15800 | | 6x=37/39 | | 3x=36/30 | | 4+3(x–1)=2(x–2) | | 10x-5+2x=7 | | (1/4)*x-1=2x | | 1/4*x-1=2x | | x+6+x=49 |